Influence of land use/occupation on water quality in the Trussu river valley, Ceará, Brazil - Araújo Neto, José; Andrade, Eunice; Palácio, Helba; de Sales, Maria; Maia, Anthony Rafael (Revista Ciência Agronômica, 2016)
The growing pressure on water resources has reduced its availability as regards quality. Data was investigated for two different periods, with the aim of evaluating the influence of the use and occupation of space on the temporal dynamics of the quality of surface and groundwater in the perennialised valley of the Trussu River in the State of Ceará, Brazil. The first period was from September 2002 to February 2004 and the second from April 2013 to April 2014. Twenty-two water samples were taken from nine sampling stations, five on the surface and four underground. The same stations were considered, monitoring 12 attributes of water quality for a total of 2,376 analyses. Temporal dynamics were characterised employing a technique of multivariate statistics: hierarchical cluster analysis (HCA). The three groups formed by the surface water were independent of collection time, indicating that there was no significant change at a level of 1%. The main differences between the periods of monitoring were seen in the groundwater, with a reduction in the values of EC, Na+, Cl- and HCO3-, and an increase in the concentrations of the PO43- and NO3- ions during the second period, forming two distinct groups: group 1 comprising the water collected during the first period, and group 2 the water collected from April 2013 to April 2014. These results reflect changes in the quality of the groundwater due to an increase in agricultural area, and show that the change in land use had a greater impact on the groundwater.